Analisis Tingkat Pemanfaatan Optimal Ikan Kerapu (Epinephelus spp.) untuk Perikanan Berkelanjutan Kabupaten Bangka - Yandi, Misri; Monischa Br Sebayang; Ahmad Desta Ardiansyah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The sustainable management of fishery resources is critical to maintaining ecological balance and long-term economic benefits. This study aims to estimate the optimal level of exploitation of grouper (Epinephelus spp.) in the waters of Bangka Regency using a surplus production model to determine the Maximum Sustainable Yield (MSY). Production and effort data from 2020 to 2024 were analyzed using a Schaefer model to derive the MSY curve. The analysis reveals that the MSY for grouper in this region is 1,577.2 tons, corresponding to an optimal fishing effort (f_opt) of 20,742 standardized trips. Notably, actual fishing efforts and production in 2022 exceeded the sustainable threshold, indicating a risk of overfishing, while efforts in 2023 and 2024 remained beyond the optimal level but with declining yields. These trends suggest the onset of growth overfishing if not addressed through adaptive management. The study concludes that current fishing practices in Bangka may surpass the sustainable capacity of grouper stocks, and immediate management interventions are recommended to regulate fishing effort in alignment with MSY estimates. This research provides scientific support for implementing evidence-based fisheries policies to ensure sustainability and resilience of marine resources in the region,